Faculty-TA collaborative tool - Lew, Xun Yi (Nanyang Technological University, 2024)
Professors and teaching assistants have had trouble when communicating through email due to the inefficiency of emailing and the difficulty of tracking information from the thousands of emails in their inboxes. This project aims to develop a web application that can solve the problems of using email and make the lives of professors and teaching assistants easier.